2011
DOI: 10.2174/1745017901107010167
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Review of Metanalytic Studies with Repetitive Transcranial Magnetic Stimulation (rTMS) for the Treatment of Major Depression

Abstract: Background:Major Depression (MD) and treatment-resistant depression (TRD) are worldwide leading causes of disability and therapeutic strategies for these impairing and prevalent conditions include pharmacological augmentation strategies and brain stimulation techniques. In this perspective, repetitive transcranial magnetic stimulation (rTMS) is a non-invasive brain stimulation technique with a favorable profile of tolerability which, despite being recently approved by the Food and Drug Administration (FDA) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 64 publications
6
53
0
Order By: Relevance
“…This study also confirmed that rTMS is a safe stimulation method in terms of the side effect profile; however, transient headache was found to be the most common side effect, which is consistent with the current data [2,29].…”
Section: Discussionsupporting
confidence: 91%
“…This study also confirmed that rTMS is a safe stimulation method in terms of the side effect profile; however, transient headache was found to be the most common side effect, which is consistent with the current data [2,29].…”
Section: Discussionsupporting
confidence: 91%
“…However, it is usually assumed that multiple daily applications in stroke may lead to a build-up of effects that are larger and more persistent. The main evidence in favour of this comes from studies of rTMS to treat depression: a single session, or even 2 weeks daily treatment with rTMS has little effect on symptoms over and above placebo, whereas longer (>4 weeks) treatments can improve symptoms for several months (Dell'Osso et al, 2011;Galletly et al, 2012). Thus most recent clinical trials of tDCS have employed several days or weeks of repeated treatment with rehabilitation programmes in an attempt to maximise outcome (Lee and Chun, 2014;Viana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The first involves the application of strong Tesla-level pulsed fields, TMS (Transcranial Magnetic Stimulation). There is strong evidence that the strategic application of these focal fields over discrete areas can affect cognition [1] and affective [2] behaviours. The mechanism by which these change occur is assumed to be a Faraday-like induction of relatively strong electric currents within populations of neurons.…”
Section: Introductionmentioning
confidence: 99%